EFEK ANTIINFLAMASI PERASAN KERING BUAH Morinda citrifolia Linn SECARA PER ORAL PADA TIKUS PUTIH - Wahjo Dyatmiko; Suprapto Maat; Idha Kusumawati; Gemparing Bayu Wiyoto (The East Java Biological Society, 2003)
Research on anti inflammatory activity of the fruit of Morinda citrifolia Linn. Or known as ‘pace’ in Indonesia language has been done by using three methods of assays i.e. anti inflammatory bioactivity assay by measuring the reduction of carrageen-induced oedema in rats; analgesic bioactivity assay using writhing test method on mice; and vascular permeability bioactivity assay on mice induced by acetic acid.Results showed that dried juice of the fruit at the dose 1500 mg/kg body weight decreased the volume of oedema up to 64% and reduced the pain up to 54%. At the dose 2100 mg/kg body weight the dried juice reduced the vascular permeability up to 72%.